A BI-OBJECTIVE REDUNDANCY ALLOCATION PROBLEM WITH TIME-DEPENDENT FAILURE RATES - Sharifi, Mani; Shojaie, Arefe; Naserkhaki, Sajjad; Shahriari, Mohammadreza (International Journal of Industrial Engineering: Theory, Applications and Practice, 2018)
This study considers a bi-objective redundancy allocation problem without component mixing (RAPCM) for a series-parallel system containing S subsystems. Currently the majority of the available models in this field, are single objective with an exponential distribution function in component failure, but in the mathematical model of our solution, it is hypothesized that the redundancy policy is active. As the failure rate of system components depends on the number of working components, decreasing the number of active components increases the failure rate of working components. The structure of the system studied in this research, is series-parallel with k-out-of-n subsystems and time dependent components failure rates. This problem aims to select the component type among available components and the number of allocated ones to each subsystem with weight and volume constraints because of maximizing system reliability and minimizing system costs. Since the model presented in this paper is nonlinear and complicated, we suggest the Non-dominated Sorting Genetic Algorithms II to solve the problem.